PENGARUH KEMAMPUAN PEMAHAMAN NILAI-NILAI PANCASILA TERHADAP SIKAP SOPAN SANTUN PESERTA DIDIK DISEKOLAH DASAR - Nurmitasari Nurmitasari; Antika Saputri; Ning Apritra; Umi Warohmah; Singgih Saputra (LPPM Universitas Cipta Mandiri, 2026)
This study aims to determine the influence of students’ understanding of Pancasila values on their politeness attitudes in elementary schools. The background of this research is based on the phenomenon of declining politeness among students, indicating that the understanding and practice of Pancasila values in daily life have not been optimal. This research employed a quantitative approach with a simple linear regression method. The population consisted of all fifth-grade students at UPT SDN 3 Margodadi, totaling 33 respondents, using a total sampling technique. Data were collected through a test of Pancasila values comprehension and an observation sheet assessing politeness behavior. The results of data analysis show a very strong influence between the understanding of Pancasila values (X) and students’ politeness attitudes (Y), with a coefficient of determination of 99.8%. The results of the validity, reliability, normality, and linearity tests indicate that the research instruments are valid, reliable, normally distributed, and have a significant linear relationship. Thus, the higher the students’ understanding of Pancasila values, the higher their level of politeness. This study emphasizes the importance of continuously instilling Pancasila values in the learning process as the foundation for developing students’ character to become virtuous, polite, and well-mannered individuals in accordance with the noble identity of the Indonesian nation.